THE INFLUENCE OF BRAND IMAGE AND SERVICE QUALITY ON REPURCHASE INTENTION THROUGH CUSTOMER VALUE AS AN INTERVENING VARIABLE IN CONSUMERS OF HILON PRODUCTS IN MEDAN CITY - Sembiring, Aprianta Raskami; Ginting, Paham; Rini, Endang Sulistya (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
This research aims to determine the influence of brand image and service quality on repurchase intention through customer value. The number of samples is 100 respondents with the sampling technique using a purposive sampling technique. This type of research is explanatory research. The research results show that brand image has a positive and significant effect on repurchase intention. Service quality has a positive and significant effect on repurchase intention. Apart from that, brand image has a positive and significant effect on customer value and service quality has a positive and significant effect on customer value.